Project-Based Learning Model Increases Student Creativity and Learning Outcomes in Pancasila and Citizenship Education Learning - Peri Pirdaus (Journal of Education Reseach and Evaluation, 2024)
The phenomenon of a lost generation results from less than optimal education services for children during the pandemic season. It causes low student learning outcomes. This research aims to analyze the project-based learning model on students' creativity and learning outcomes in learning Pancasila and citizenship education in high school. This research is quasi-experimental or quasi-experimental with a pretest-posttest control group design. The population in this study was 386 class XI students. The sample selection for the experimental and control groups used a random sampling technique, totaling 70 students. Data collection methods use questionnaires and tests. Data collection instruments use questionnaires and test questions. The analysis test uses the independent sample T-test and descriptive analysis. The research results showed that there was a significant difference in student creativity between the experimental class and the control class. There is a significant difference between the experimental and control classes' post-test results. It was concluded that applying the project-based learning model significantly influenced the creativity and learning outcomes of class XI MIPA-1 students in high school. This research implies that teachers can apply active and reflective learning models, such as project-based learning, to make learning more meaningful.